Quality interviewing - Maddux, Robert B. (Crisp Pub. Menlo ParkUS, 1994)
Introduces the basic concepts of conducting a professional job interview. Supports the businesslike interview style. Explains how to plan for an interview and make the best selection decisions after. Provides case histories with author's comments.